Implementasi Pancasila Sebagai Fondasi Pendidikan Dalam Kurikulum Merdeka - Mila Sari Tanjung (Politeknik Kampar, 2024)
The independent curriculum is a curriculum that is based on developing the profile of students so that they have good souls and values contained in the Pancasila principles in his life. In the independent curriculum there is P5 (Project for Strengthening the Profile of Pancasila Students) which is learning that aims to create Pancasila students who are able to behave in accordance with Pancasila values. The type of research used is qualitative research using a literature study approach in the form of books, notes, journals, reports of relevant research results, as well as the results of observations. The results of the analysis show that the values contained in Pancasila form a unified whole which is the educational foundation for the government to create a Pancasila student profile program in the independent curriculum. There are six aspects of the Pancasila Student Profile formulated by the Ministry of Education and Culture, namely: 1) Faith, Devotion to God Almighty and Noble Character, 2) Creativity, 3) Mutual Cooperation, 4) Global Diversity, 5) Critical Reasoning, 6) Independence. Pancasila values can be a reference in building the character and morals of the Indonesian people, especially students. This can be implemented through education that applies Pancasila values in all curricula and learning activities. Apart from that, introducing and understanding the values of Pancasila from an early age will help in forming strong character in students.